Alternative Forms for Promotion and Dissemination of Good Management Practices - Zahariev, Elenko (Journal of Economic Development, Environment and People, 2015)
At the present stage actuality of the problem is predetermined by the needs of the real management practice in organizations and the need to offer theoretical and practical knowledge to enable it methodologically correct and methodically right to implement appropriate changes in the management of the particular organization. The article is devoted to one aspect in the field of management - creating a new form of organization of management (called new favorite) - international managerial architecture. It argues that it was dictated by poor management of institutional and corporate level, the lack of adequate professional standards, control and monitoring of the activities of managers. An attempt is made to give a reasoned response to relatively basic question: "Predetermination or managerial obfuscation are alternative forms of promotion and dissemination of good management practices?". The goal is to answer the question in a relatively unbiased approach, insofar as possible minimizing subjectivity in the treatment of problems. Finally, certain results of the proposed thesis on the need for the creation of NIMA are discussed- structure and structural parameters. The discussions are based on the experience in the Republic of Bulgaria taken as an example situation.